Elasticity and breaking strength of synthetic suture materials incubated in various equine physiological and pathological solutions. (20th November 2013) - Kearney, C. M.; Buckley, C. T.; Jenner, F.; Moissonnier, P.; Brama, P. A. J.
Summary Reasons for performing study Selection of suture material in equine surgery is often based on costs or subjective factors, such as the surgeon's personal experience, rather than objective facts. The amount of objective data available on durability of suture materials with regard to specific equine physiological conditions is limited. Objectives To evaluate the effect of various equine physiological and pathological fluids on the rate of degradation of a number of commonly used suture materials. Study design In vitro material testing. Methods Suture materials were exposed in vitro to physiological fluid, followed by biomechanical analysis. Three absorbable suture materials, glycolide/lactide copolymer, polyglactin 910 and polydioxanone were incubated at 37°C for 7, 14 or 28 days in phosphate‐buffered saline, equine serum, equine urine and equine peritoneal fluid from an animal with peritonitis. Five strands of each suture material type were tested to failure in a materials testing machine for each time point and each incubation medium. Yield strength, strain and Young's modulus were calculated, analysed and reported. Results For all suture types, the incubation time had a significant effect on yield strength, percentage elongation and Young's modulus in all culture media (P<0.0001). Suture type was also shown significantly to influence changes in each of yield strength, percentage elongation and Young's modulus in all culture media (P<0.0001). While the glycolide/lactide copolymer demonstrated the highest Day 0 yield strength, it showed the most rapid degradation in all culture media. For each of the 3 material characteristics tested, polydioxanone showed the least variation across the incubation period in each culture medium. Conclusions The duration of incubation and the type of fluid have significant effects on the biomechanical properties of various suture materials. These findings are important for evidence‐based selection of suture material in clinical cases.